Features extraction using airborne LiDAR data in urban area - Nuramalina Mohd. Fadil, 1994-, author; Zamri Ismail, supervisor; Fakulti Geoinformasi dan Harta Tanah (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2017